Uji Kualitatif Aktivitas Radikal Bebas DPPH dari Daun Penggugut (Knema pallens W.J.deWilde): Qualitative Test of DPPH Radical Scavenging Activity from Penggugut Leaves (Knema pallens W.J.deWilde) - Annisa Anugrah Putri; Hifdzur Rashif Rija’i; Laode Rijai (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Penggugut (Knema pallens W.J. deWilde) is an endemic plant from Kalimantan belongs to Myristicaceae or the nutmeg family. Penggugut can be found in habitats like lowland forest, sandy forests and mangroves. The efficacy and activity of penggugut especially the leaves, have not been widely known or studied. So that make the purpose was to know about the percentage yield of extract and fraction from penggugut leaves and to know the activity of Radical Scavenging DPPH from penggugut leaves. The methods used include extraction, liquid-liquid fractination and TLC by spraying DPPH. The results there are percentage of yield : methanol extract is 8,04%, n-hexane fraction is 28,9%, ethyl acetate fraction is 7,83% and n-butanol fraction is 9,8%. In the qualitative test, it was found that the spots have activity of Radical Scavenging were marked with yellow spots on a purple background, there are in the methanol extract have 4 spots with Rf values (0,07; 0,14; 0,29; 0,43), the n-hexane fraction have 3 spots with Rf values ??(0,1; 0,21; 0,43), the ethyl acetate fraction have 5 spots with Rf values ??(0,07; 0,17; 0,29; 0,43; 0,53) and the n-butanol fraction did not get any spots.